2023
DOI: 10.3390/ijms24021798
|View full text |Cite
|
Sign up to set email alerts
|

The Bph45 Gene Confers Resistance against Brown Planthopper in Rice by Reducing the Production of Limonene

Abstract: Brown planthopper (BPH), a monophagous phloem feeder, consumes a large amount of photoassimilates in rice and causes wilting. A near-isogenic line ‘TNG71-Bph45’ was developed from the Oryza sativa japonica variety ‘Tainung 71 (TNG71) carrying a dominant BPH-resistance locus derived from Oryza nivara (IRGC 102165) near the centromere of chromosome 4. We compared the NIL (TNG71-Bph45) and the recurrent parent to explore how the Bph45 gene confers BPH resistance. We found that TNG71-Bph45 is less attractive to BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This did not occur in three hybrids (IR80814H, IR81954H, and IR81955H) that showed heterobeltiosis for resistance, thereby further suggesting that quantitative resistance to planthoppers is achievable through the careful selection of parental lines. In our oviposition experiments, plant size affected one of two cases of heterosis for antixenosis resistance; suggesting that there was little effect of breeding on other factors, such as plant volatiles or silicon-based defenses [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] that are involved in antixenosis resistance. The experiments indicate the importance of separating physiologically-dependent susceptibility (e.g., related to size, growth rates, etc.)…”
Section: Discussionmentioning
confidence: 86%
“…This did not occur in three hybrids (IR80814H, IR81954H, and IR81955H) that showed heterobeltiosis for resistance, thereby further suggesting that quantitative resistance to planthoppers is achievable through the careful selection of parental lines. In our oviposition experiments, plant size affected one of two cases of heterosis for antixenosis resistance; suggesting that there was little effect of breeding on other factors, such as plant volatiles or silicon-based defenses [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ] that are involved in antixenosis resistance. The experiments indicate the importance of separating physiologically-dependent susceptibility (e.g., related to size, growth rates, etc.)…”
Section: Discussionmentioning
confidence: 86%
“…As a result, the identification and molecular breeding of rice germplasms that possess BPH-resistance genes (referred to as Bph/bph genes) are regarded as the optimal approach for effectively controlling and managing BPH [3]. Up to the present, a total of 45 BPH resistance loci have been documented across various rice cultivars and wild-rice species [4]. Amongst them, bph2/Bph26 [5], Bph3/Bph17 [6], Bph6 [7], Bph9 [8],…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new sources of resistance to BPH are a continuous requirement of the rice breeding program. In this study [ 15 ], a major effect-resistance gene, Bph45, located on chromosome 4, was identified from Oryza nivara by genetic mapping. A near-isogenic line (NIL) for this gene in a japonica varietal background was compared with its recurrent parent with respect to the emitted volatile organic compounds (VOCs) in order to understand the underlying resistance mechanism.…”
Section: Introductionmentioning
confidence: 99%